Emotional Labor, Job Satisfaction, and Burnout in Medical Technicians: Insights from the Korea Veterans Health Service - Eun-Taek HONG; Yo-Han SEO (Korean Journal of Clinical Laboratory Science)
Previous research on emotional labor, job satisfaction, and burnout in hospitals has focused primarily on nurses or medical technicians as a single occupational group. On the other hand, recognizing the diverse experiences within different medical technician roles necessitates a more nuanced analysis. This study examined the correlation among emotional labor, job satisfaction, and burnout in medical technicians to provide foundational data for human resource management. The participants included 570 medical technologists, radiology technologists, physical therapists, and dental hygienists working in six hospitals under the Korea Veterans Health Service in July 2022. A standardized self-administered questionnaire was used, with 290 participants responding (response rate: 50.9%). Model I analyzed burnout with emotional labor, job satisfaction, and subjective health status as independent variables. Model II added the sociodemographic characteristics and job-related factors influencing current job choices or potential job changes. The factors influencing burnout varied across occupations. In Model II, burnout was significantly associated with medical technologists’ job satisfaction (B=-0.203, P=0.014), radiology technologists’ emotional labor (B=0.546, P=0.024), physical therapists’ emotional labor (B=0.466, P<0.001), subjective health status (B=3.234, P=0.029), and dental hygienists’ subjective health status (B=5.788, P=0.030). These results highlight the need for tailored management strategies and further research.